The impact of growth on the transmission of patience - Domenico Delli Gatti; Jakob Grazzini; Domenico Massaro; Fabrizio Panebianco (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2022)
Patience affects economic growth, no news. This paper investigates the opposite causal relationship, i.e., how growth influences patience. We propose a simple theoretical framework where heterogeneous parents may choose to transmit their cultural trait - patience - to their offspring. Our model shows that parental effort to educate children to patience positively depends on economic growth. We test empirically this result using both country-level and individual data and show that, coherently with the model's prediction, growth has a significant impact on the effort to teach patience.
Keywords: D15; D91; E21; O47; 330; Growth; Patience; Cultural transmission